Let them eat junk : how capitalism creates hunger and obesity - Albritton, Robert, 1941- (Pluto Press ; Distributed in the United States of America exclusively by Palgrave Macmillan, 2009)
A thorough explanation of how the capitalist system creates simultaneous hunger and obesity.